Communication Technology Backwash toward Interpersonal Communication Behavior - Agustinus Rustanda (Communication Sphere, 2015)
ABSTRACTThe development of information and communication technology gives impact to theusers. It gives positive impacts and negative ones as well. There are harmful effects ofcommunication technology toward the change of communication behavior such as thedecline of the quality of face to face interpersonal communications, the destruction of familyto the loss of power and authority, the increase of crimes among youngsters that will lead themto sexual harassment. The problem of this research is formulated as is there a positive andsignificant effect between the development of communication technology to the change ofcommunication behavior. The objective of this research is to find out and analyze those effects.Incidental sampling is implemented to collect data for this research. There were 623valid questionnaires which will be analyzed in this research. These will be presented throughdescriptive statistic and statistical analysis. This research is a quantitative method research withlinear simple regression by means of SPSS 20. The result of the research showed that 29%variance of the change of communication behavior can be explained by the change of score incommunication technology variable whereas 71% is caused by other factors. Correlations (R0.539) with degree of significance 0.0000.05 became the proof to reject H0. It means that thehypothesis there is an effect between the development of communication technology towardsthe change of communication behavior cannot be rejected. The findings of this research are thechange of communication such as openness, instance, practicality, self-confidence, innovation,inclusion, and technological literacy. On the other hand, there are negative communicationbehaviors such as extravagance, deficiency of privacy, individualism, procrastination,anxiety, indolence, insensibility, decline of reading habit, and emotional.Keywords: Communication Technology, Interpersonal Communication Behavior, Backwash